Exploring the Relationship Between Internal Governance and CSR Performance: Insights from Literature and Emerging Trends - Dadang Irawan; Benardi Benardi (Jurnal Pajak dan Analisis Ekonomi Syariah, 2025)
This qualitative literature review explores the relationship between internal governance mechanisms and corporate social responsibility (CSR) performance. Drawing insights from recent studies, the review identifies key governance elements—such as board independence, ethical leadership, and audit committees—that enhance CSR outcomes by fostering accountability and stakeholder alignment. Additionally, emerging governance trends, including digital tools and ESG integration, are examined to understand their impact on CSR performance. Comparative analysis highlights the contextual differences across industries and regions, emphasizing the role of cultural, regulatory, and institutional factors in shaping governance-CSR dynamics. The findings underscore the importance of robust and context-specific governance strategies to optimize CSR initiatives and achieve sustainable development. This review also discusses its limitations and suggests directions for future research, including the integration of emerging technologies and sector-specific analyses.